Customer Satisfaction Analysis of Project Performance at PUPRKIM Bali Province - Astana, I Nyoman Yudha; Hidayati, Anissa Maria; Sastra, I Nyoman Gede Sadu (Journal of Asian Multicultural Research for Economy and Management Study, 2023)
One factor that has a significant impact on customer satisfaction is project performance. A government agency that also serves as a client for infrastructure development is the PUPRKIM. The objectives of this study are to identify the project performance factors at the PUPRKIM of Bali Province, to ascertain the relationship between project performance and customer satisfaction at the PUPRKIM of Bali Province, and the contractor's efforts to raise customer satisfaction at the owner. Customers at the PUPRKIM in Bali Province as a respondent comprised of 45 contract signing officers, board coordinators, and board members made up the research sample. Questionnaires were used during the data collection process. Factor analysis and partial least squares analysis of structural equation models are data processing techniques. The test results demonstrate that: the contractor's efforts to increase customer satisfaction by enhancing project performance; project performance has a positive and significant impact on customer satisfaction; and project performance has a positive and significant impact on contractor planning and strategy, worker capabilities, and supporting materials and equipment. The capacity of the contractor's workforce, human resources, and auxiliary supplies and equipment needs to be strengthened.